Human papillomavirus vaccine efficacy in the prevention of anogenital warts: systematic review and meta-analysis. - Tejada, Romina A (2017)
Objective: To review evidence on the efficacy of HPV vaccines in the prevention of non-cancer lesions (anogenital warts [AGW], recurrent laryngeal papillomatosis and oral papillomatosis). Materials and methods: We conducted a systematic review of randomized trials. We performed random effect models and effects were reported as relative risks (RR) and their confidence intervals (95%CI) following both intention to treat (ITT) and per protocol (PP) analyses. Results: We included six studies (n=27 078). One study was rated as high risk of bias. One study could not be included in the meta-analysis because it provided combined results. We found that quadrivalent vaccine reduced the risk of AGW by 62% (RR: 0.38, 95%CI:0.32-0.45, I2:0%) in the ITT analysis and by 95% (RR: 0.05, 95%CI:0.01-0.25, I2:66%) in the PP analysis. Subgroup analyses of studies in women or with low-risk of bias provided similar results. Conclusion: HPV quadrivalent vaccine is efficacious in preventing AGW in men and women.